AI Techniques for Near Real-Time Monitoring of Contaminants in Coastal Waters on Board Future $Φ$ sat-2 Mission - Francesca Razzano; Pietro Di Stasio; Francesco Mauro; Gabriele Meoni; Marco Esposito; Gilda Schirinzi; Silvia Liberata Ullo (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing)
Differently from conventional procedures, the proposed solution advocates for a groundbreaking paradigm in water quality monitoring through the integration of satellite Remote Sensing data, Artificial Intelligence techniques, and onboard processing. While conventional procedures present several drawbacks mainly related to late intervention capabilities, the objective of what proposed is to offer nearly real-time detection of contaminants in coastal waters addressing a significant gap in the existing literature and allowing fast alerts and intervention. In fact, the expected outcomes include substantial advancements in environmental monitoring, public health protection, and resource conservation. Namely, the specific focus of our study is on the estimation of Turbidity and pH parameters, for their implications on human and aquatic health. Nevertheless, the designed framework can be extended to include other parameters of interest in the water environment and beyond. Originating from our participation in the European Space Agency OrbitalAI Challenge, this article describes the distinctive opportunities and issues for the contaminants' monitoring on the $Φ$ sat-2 mission. The specific characteristics of this mission, with the tools made available, will be presented, with the methodology proposed by the authors for the onboard monitoring of water contaminants in near real-time. Preliminary promising results are presented, along with an introduction to ongoing and future work.